Participatory research why and how to involve people in research - Schubotz, Dirk. author (Los Angeles Sage Publications Ltd, 2020)
Going beyond a general introduction to offer a hands-on guide, Participatory Research empowers students to feel confident understanding and applying participatory methods to their research projects. It takes an accessible approach to explaining the theory that grounds participatory research and offers students practical strategies for how and when to choose and apply a wide range of these methods. Comprehensive yet easy to understand, this book: gives students a thorough grounding in the history and theoretical issues surrounding each method, showcases participatory research in action through extensive on-the-ground case studies, highlights the importance of ethics in research design, offering guidance on dealing with sensitive considerations in participatory research. With a sustained focus on the impact of digital technologies, this book tackles head-on the need to re-assess the way we involve people in contemporary research. It is an essential guide to better research practice for students and researchers across the social sciences
Part I: History, theory and ethics of participatory methods ; The history and nature of participatory research methods ; Theoretical perspectives on participatory research ; Approaches and populations in participatory research ; Research ethics in participatory research practice -- Part II: Applications of participatory methods ; Participatory action research ; Participatory approaches to participant observation ; Group discussion methods in participatory research ; Participatory survey methods
Includes bibliographical references and index
Keywords: Social sciences -- Research .; Research -- Methodology .; Action research .